Waterlogging of winter crops at early and late stages : impacts on leaf physiology, growth and yield : Corrigendum - Ploschuk, Rocío Antonella (2020)
Fil: Ploschuk, Rocío Antonella. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.